Innate lymphocytes: Role in alcohol-induced immune dysfunction - Ruiz-Cortes, Karla; Villageliu, Daniel N.; Samuelson, Derrick R. (Frontiers in Immunology, 2022)
Alcohol use is known to alter the number and function of immune cells, such as macrophages, neutrophils, and T-cells. Immune dysfunction has been associated with alcohol-induced end-organ damage. Since the discovery of liver-resident natural killer (NK) cells, the importance of innate lymphocytes in alcohol-associated pathogenesis has become a focus of research. Innate lymphocytes play a critical role in immunity and homeostasis; they are necessary for an optimal host response against insults including infections and cancer. However, the role of innate lymphocytes, including NK cells, mucosal associated invariant T (MAIT) cells, natural killer T (NKT) cells, gamma delta T-cells, and innate lymphoid cells (ILCs) type 1-3 remain ill-defined in the context of alcohol-induced end-organ damage. This review will address the current knowledge regarding the effects of alcohol misuse on innate lymphocytes, as well as the consequences of innate lymphocyte dysfunction on alcohol-induced end-organ damage.